Early childbirth, health inputs and child mortality: recent evidence from Bangladesh - Pushkar Maitra; Sarmistha Pal (Institute for the Study of Labor (IZA), 2007)
This paper examines the relationship between early childbearing and child mortality in Bangladesh, a country where adolescent childbearing is of particular concern. We argue that effective use of specific health inputs could however significantly lower child mortality rates even among adolescent women. This offers an attractive policy option particularly when compared to the costly alternative of delaying age at marriage. In particular, we find that women having early childbirth tend to use health inputs differently from all other women. After correcting for this possible selectivity bias, the adverse effects of early childbirth on child mortality are reversed. The favourable effects of use of health inputs however continue remain statistically significant.
Keywords: 330; Mütter; Jugendliche; Kindersterblichkeit; Gesundheitsversorgung; Bangladesch